The Teacher`s Authority in the Students and Teachers Comprehension - Smilga, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Changes in education alter the relations between teachers and students – accents of values are changing. When putting student in the centre it is important not to neglect teacher’s personality which is a necessity for the growth and education of young people. Nowadays the influence of the authority is disappearing in many areas. But a teacher cannot carry out his/her professional duties without authority. The goal of the research is to determine the student’s and teacher’s understanding of the teacher’s authority. Does teacher have to be an authority for his/her students? How teacher’s authority should manifest itself? Results of processing and analysis of data from many surveys are shown in the research. The findings of the study show that students and teachers consider that the authority is the essential for teacher’s professional activity.